2020
DOI: 10.1007/s00392-020-01658-1
|View full text |Cite
|
Sign up to set email alerts
|

Noncalcified plaque burden quantified from coronary computed tomography angiography improves prediction of side branch occlusion after main vessel stenting in bifurcation lesions: results from the CT-PRECISION registry

Abstract: Objectives To assess the incremental value of quantitative plaque features measured from computed tomography angiography (CTA) for predicting side branch (SB) occlusion in coronary bifurcation intervention. Methods We included 340 patients with 377 bifurcation lesions in the post hoc analysis of the CT-PRECISION registry. Each bifurcation was divided into three segments: the proximal main vessel (MV), the distal MV, and the SB. Segments with evidence of coronary plaque … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
2
5
1
Order By: Relevance
“…In this context, the visual CTA-derived V-RESOLVE score is yet another predictor (after quantitative CTA-derived RESOLVE score, Medina class with any involvement of the proximal MV and SB plaque, and the presence of any plaque within the first 5 mm of SB segment on coronary CTA) of SB occlusion in coronary bifurcation intervention. 20,21 Discriminative Performance of CTA-derived V-RESOLVE Score Our data confirmed the ability of CTA-derived V-RESOLVE score to stratify lesions into high-risk group and non-high-risk group of SB occlusion. Specifically, by using the cutoff value of 17 points (defined as the lowest score in quartile 4) for discrimination between high-risk group ( ≥ 17) and non-highrisk group (< 17), the incidence of SB occlusion was significantly higher in the high-risk group (18.6%) than in the non-high-risk group (3.8%).…”
Section: Predictive Accuracy Of Cta-derived V-resolve Scoresupporting
confidence: 76%
See 1 more Smart Citation
“…In this context, the visual CTA-derived V-RESOLVE score is yet another predictor (after quantitative CTA-derived RESOLVE score, Medina class with any involvement of the proximal MV and SB plaque, and the presence of any plaque within the first 5 mm of SB segment on coronary CTA) of SB occlusion in coronary bifurcation intervention. 20,21 Discriminative Performance of CTA-derived V-RESOLVE Score Our data confirmed the ability of CTA-derived V-RESOLVE score to stratify lesions into high-risk group and non-high-risk group of SB occlusion. Specifically, by using the cutoff value of 17 points (defined as the lowest score in quartile 4) for discrimination between high-risk group ( ≥ 17) and non-highrisk group (< 17), the incidence of SB occlusion was significantly higher in the high-risk group (18.6%) than in the non-high-risk group (3.8%).…”
Section: Predictive Accuracy Of Cta-derived V-resolve Scoresupporting
confidence: 76%
“…In this regard, our findings compare equally with earlier studies on the ability of the angiography-based V-RESOLVE score to predict SB occlusion during coronary bifurcation intervention (with AUC ranging from 0.75 to 0.80), and further extend the utility of coronary CTA for guiding PCI. In this context, the visual CTA-derived V-RESOLVE score is yet another predictor (after quantitative CTA-derived RESOLVE score, Medina class with any involvement of the proximal MV and SB plaque, and the presence of any plaque within the first 5 mm of SB segment on coronary CTA) of SB occlusion in coronary bifurcation intervention 20,21…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ], Grodecki et al . [ 17 ], and Opolski et al [ 18 ], as all of these studies found a significant relation between Medina score and SB occlusion in the studied cases.…”
Section: Discussionmentioning
confidence: 62%
“…However, additional quantification of noncalcified tissue might extend our knowledge of the role of valve composition in LT, as it is hypothesized that the damaged native valve tissue may induce thrombosis due to exposure of TF [ 9 , 65 ]. Until now, the association between noncalcified coronary plaque subsets with adverse cardiac events, as well as unfavorable procedural outcomes of percutaneous coronary interventions, have been well evidenced [ 66 , 67 ]. The anatomy of the aortic valve complex also does not seem to effect the LT risk, with only one study demonstrating an association between the larger diameter of Valsalva sinuses and HALT [ 15 ].…”
Section: Imaging Predictorsmentioning
confidence: 99%